A Soul by Any Other Name: The Name-Soul Concept in Circumpolar Perspective. (July 2019) - Walsh, Matthew J.; O'Neill, Sean; Riede, Felix; Willerslev, Rane
Name-soul beliefs maintain that, through a process of reincarnation, spirits of the deceased return into the bodies of newborn members of the same society. When this is recognized, the newborn or very young child is then named for the previously known ancestor or close kin relation believed to be returning (e.g., a grandfather, or an aunt). Name-soul spiritual beliefs among traditional indigenous societies residing in circumpolar regions are pervasive. These correlate with livelihoods earned through hunting, gathering, and fishing in freezing cold expanses of extreme landscape, presenting great physical challenges for traditional families over many generations. A neo-functionalist argument is proposed here, with two aspects. First, that kin ties are strongly reinforced between generations through this close association of affinity and identity, providing important emotional bonds that vitally facilitate physical survival. Second, that the sharpened spiritual power of a soul with the wherewithal to journey back offered powerful protection to the young. Drawing on detailed readings of qualitative ethnographic literature on 11 discrete societies across the region as evidence, this article compares and contrasts name-soul beliefs to better understand the extent to which very similar beliefs might have emerged independently of each other, and how these might have solved similar problems.